Increased light availability and nutrient cycling by fish provide resilience against reversing eutrophication in an agriculturally impacted reservoir. (26th July 2018) - Kelly, Patrick T.; González, María J.; Renwick, William H.; Vanni, Michael J.
Abstract: High external nutrient loads to lakes are a primary cause of eutrophication. As such, management activities in the watersheds of heavily impacted systems are commonly implemented to reduce nutrient supply to lakes with high phytoplankton biomass. Although management efforts are often successful, resilience against the reversal of eutrophication may be maintained by a variety of different drivers of phytoplankton biomass. These may include internal sources of nutrients, and increases in light availability with declining sediment loads. We used a 21‐yr dataset to examine the responses of Acton Lake, a eutrophic agriculturally impacted reservoir, to determine the relative strength of potential drivers of changes in phytoplankton biomass through time. We also identified sources of ecosystem resilience that allow the lake to remain eutrophic. Despite declining nutrient concentrations in inflow streams, chlorophyll increased in Acton Lake over approximately the first decade of our study, and remained relatively stable in the second decade. Time series modeling suggests two primary drivers of increased phytoplankton: (1) increased nutrient excretion by detritivorous fish (gizzard shad, Dorosoma cepedianum ), and (2) declining sediment loads from the watershed that reduced phytoplankton light limitation. We also identify precipitation patterns and stream discharge as being possible sources of ecosystem resilience, contributing to high loads of nutrients even if concentrations in inflow streams have declined with better management. These results suggest a more comprehensive view of management efforts to reduce eutrophication may be necessary, incorporating interactions among internal nutrient sources, climate variation, and changes in light availability.